Hepatic artery classification based on three-dimensional CT. Issue 7 (14th February 2020) - Yan, J; Feng, H; Wang, H; Yuan, F; Yang, C; Liang, X; Chen, W; Wang, J
Abstract: Background: Precise classification of the hepatic artery is helpful for preoperative surgical planning in hepatobiliary–pancreatic surgery. However, the anatomy of hepatic arteries is variable. This study investigated anatomical variation using three-dimensional visualization and evaluation (3DVE) to develop a nomenclature system. Methods: The origin and course of the hepatic artery were tracked and analysed by using three-dimensional visualization of CT images acquired between 2013 and 2017. The new classification and nomenclature system, named CRL, was developed based on the origins of the common, right and left hepatic arteries. Results: Scans from 770 adults were evaluated. Preoperative 3DVE correlated better with surgical findings than the original CT images alone. Using the CRL classification system, hepatic arteries were divided into nine subtypes. Only 87·4–89·2 per cent of the hepatic arteries of 610 living-donor liver transplant donors were depicted in Michels', Hiatt's or Varotti's classification, compared with 100 per cent identified by the CRL classification. The CRL classification was validated against external data sets from previous studies, with 99·6–100·0 per cent of patients classified by the CRL system. Conclusion: The CRL classification covers hepatic artery variants and may be used for planning liver surgery. Graphical Abstract: This study aimed to investigate the anatomical variations of the hepatic artery using three-dimensional visualization and evaluation, and to develop a new nomenclature system. The CRL classification of the hepatic artery could represent a compelling tool for precise preoperative planning in hepatobiliary–pancreatic surgery and liver transplantation. CHA, common hepatic artery; LHA, left hepatic artery; RHA right hepatic artery; PHA, proper hepatic artery; rRHA, replaced right hepatic artery; GDA, gastroduodenal artery; SMA, superior mesenteric artery; aRHA, accessory right hepatic artery; rLHA, replaced left hepatic artery; LGA, left gastric artery; aLHA, accessory left hepatic artery. Good for surgical planning